Socio-Cultural Diversity in the Form of Digital Comics for Fourth Grade Students: Validity and Feasibility - Ni Kadek Dessy Riris Andryani; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2021)
The appearance of the book that is less attractive makes students bored in learning. So the need for the application of learning media can help students understand abstract concepts, such as digital comics. This study aimed to develop digital comic learning media on the socio-cultural diversity of fourth-grade elementary school students. The subject of this research is digital comic media, and the object of this research is the validity of the digital comic media that has been developed. This study used a questionnaire method by providing an assessment sheet instrument given to 2 media expert test lecturers, two material expert test lecturers, and two teachers as practitioners. The instrument used to measure the validity of digital comic media is a rating scale in an expert's digital comic media assessment sheet. The data obtained were then analyzed using the mean formula to determine the average validity score of digital comic media. The results of the average validity score of digital comic media obtained from material experts, there is an average validation score as a whole is 4.8, media experts have an average overall validation score of 4.8 and expert practitioners have an average validation score overall is 5.7 with very good qualifications. Based on the results of this analysis, it can be said that digital comic media developed on the topic of socio-cultural diversity are declared valid and suitable for use in student learning.